Health and disease concepts: an approach to health development - Samlee Plianbangchang (Journal of Health Research, 2018)
Purpose - Health for all is an ideal goal that all governments aspire to reach. The purpose of this paper is to assess the definitions of the key terms used to better appreciate the role of the WHO member states in their efforts to achieve improved healthcare systems that suit each nation’s particular needs. Design/methodology/approach - Definitions of the terms disease, illness and health are discussed against health concepts as a means of assessing the most effective approach toward achieving an effective universal healthcare system. Findings - Universal health and treatment of sickness and disease have improved globally, but the target of achieving total wellness still remains as a goal for the future and may be impeded by diseases that have not yet evolved. The implementation of a universal health coverage system is a positive step toward achieving the goals of health and wellness for the present times. Originality/value - This is a commentary piece.